Evaluation of the infant spine by direct sagittal computed tomography. - Altman, N; Harwood-Nash, D C; Fitz, C R; Chuang, S H; Armstrong, D (American Journal of Neuroradiology, 1985)
Direct sagittal computed tomography (CT) and metrizamide myelography, in addition to standard axial CT, have proven most useful in evaluation of complex anomalies of the infant spine. Direct sagittal CT was performed by placing the entire infant sideways and supine within the gantry after metrizamide was injected. This technique was performed in six infants with diagnoses of lipoma with dysraphism, lipomyelomeningocele, lipomyelocystocele, lumbosacral agenesis with cord regression, capillary hemangioma, and vertebral osteomyelitis. The technique showed the relation and/or extension of lesions in the dorsal ventral plane, particularly the presence or absence of subarachnoid, enteric, or genitourinary communication. Spinal and paraspinal anatomic detail was also demonstrated beautifully.